factorise the following by proper substitution?

Asked by anandgoyal | 4th Jun, 2008, 10:30: AM

Expert Answer:

Solution

            Let y2 - 2y =a  and  z-a = b ,  then( y2-2y)2  - 3 ( y2-2y)(z-a) +2 ( z-a) will be written as a2- 3ab+ 2b2

           a2 -ab - 2ab+2b2  = a ( a- b) - 2b( a -b )  = ( a - b ) ( a- 2b)  substituting for a and b

           (y2 -2y-z + a) (y2 -2y-2z +2a)   answer

Answered by  | 4th Jun, 2008, 11:33: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.